Development and anti-swing control of an automated measurement robot system for multi-stud tensioning machine. Issue 8 (3rd August 2017) - Li, Haoyuan; Li, Meng; Duan, Xingguang; Gao, Liang; Cui, Tengfei; Guo, Yanjun
ABSTRACT: During nuclear power plant maintenance, the multi-stud tensioning machine is used to perform opening/sealing the cap of the reactor pressure vessel. This process incorporates elongations of 58 studs, whose extension values are monitored in real time by measurement meters. Conventionally, the placements of the meters are performed by human labor, which is time consuming and radioactively hazardous. In this paper, we introduce an automated measurement robot system, consisting of 58 node robots and multiple field bus based distributed control devices, to complete meter placement and data acquisition tasks without human involvement in the hazardous working site. In order to eliminate the swing phenomenon of the wire-driven meter adaptor on the robot distal end, extra-insensitive input shaper is employed for robot motion control, thus saving the overall operation time from traditionally over 10 minutes to less than 22 s.